The symbolic language of Akhavaans poem, a place for promoting the force of expression and its influence on readersâ mind - محمد خاکپور (مطالعات زبانی و بلاغی)
The changing of Nima’s way from romanticism to social symbolism, which was associated with refining and mixed with deep poetic meditation, caused to form this new movement (social Symbolism) in new Persian poetry. Following Nima, some of his disciples who, in reason of the entrance of artist’s ambiguity in the poetry and his depth and polysemy, had no interest in expressing their understanding and interpreting political and social questions with frankness, resort to symbolization that means going away from objectivity and getting close to subjectivity. Magnificence and greatness of Akhavan and the inflorescence of his artistic talent was synchronizing it with such delicate historical and literal period. He could recognize the border between device and the secret of eternity of the artistic works because of his acquaintance with Nima’s innovations and creativities. In conclusion, he tried to expose the social questions and effects so, with a symbolic expression, he avoided his poetry from falling in to abyss of routine.